2012
DOI: 10.1029/2011gb004085
|View full text |Cite
|
Sign up to set email alerts
|

The relative contribution of fast and slow sinking particles to ocean carbon export

Abstract: [1] Particulate organic carbon (POC) generated by primary production and exported to depth, is an important pathway for carbon transfer to the abyss, where it is stored over climatically significant timescales. These processes constitute the biological carbon pump. A spectrum of particulate sinking velocities exists throughout the water column, however numerical models often simplify this spectrum into suspended, fast and slow sinking particles. Observational studies suggest the spectrum of sinking speeds in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
251
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 182 publications
(273 citation statements)
references
References 63 publications
20
251
2
Order By: Relevance
“…Satellite chlorophyll imagery and horizontal velocities (obtained using a 150-kHz Vessel-Mounted Acoustic Doppler Current Profiler) confirmed that all of the traps were advected along the edge of an anticyclonic eddy for 50 km before surfacing within 3.5 km of each other. Measured POC flux at 50 m (84±8 mg C m -2 d -1 ) was close to independently derived estimates using 234 Th budgets and studies of collected marine snow particles (99±41 and 146±26 mg C m -2 d -1 , respectively) 13 . Flux attenuation with depth followed the Martin curve (F = F 100 (z/100) b ) 9 with b = -0.70 (p<0.01, R 2 =0.95, n=5) and was consistent with observations in the Pacific Ocean (b: -0.50 to -1.38; Fig.…”
supporting
confidence: 80%
“…Satellite chlorophyll imagery and horizontal velocities (obtained using a 150-kHz Vessel-Mounted Acoustic Doppler Current Profiler) confirmed that all of the traps were advected along the edge of an anticyclonic eddy for 50 km before surfacing within 3.5 km of each other. Measured POC flux at 50 m (84±8 mg C m -2 d -1 ) was close to independently derived estimates using 234 Th budgets and studies of collected marine snow particles (99±41 and 146±26 mg C m -2 d -1 , respectively) 13 . Flux attenuation with depth followed the Martin curve (F = F 100 (z/100) b ) 9 with b = -0.70 (p<0.01, R 2 =0.95, n=5) and was consistent with observations in the Pacific Ocean (b: -0.50 to -1.38; Fig.…”
supporting
confidence: 80%
“…The probable composition of sinking aggregates (the high content of lithogenic material and the low amount of relatively buoyant OM), as well as their sinking velocity (∼ 24-86 m d −1 ; Bressac et al, 2012) suggest low specific carbon remineralization (Riley et al, 2012). Furthermore, the inherent sporadic character of the lithogenic carbon pump may play a fundamental role in carbon sequestration (Ragueneau et al, 2006) since episodic events may lead to the rapid sinking of particles that will not be fully exploited by the deep sea bacterial community (Hansell and Ducklow, 2003;Nagata et al, 2000Nagata et al, , 2010.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been demonstrated that minerals could increase the velocity at which aggregates sink (e.g., De La Rocha and Passow, 2007;De La Rocha et al, 2008;Thomalla et al, 2008;Engel et al, 2009b; and drive large POC flux events (e.g., Thunell et al, 2007;Lee et al, 2009;Sanders et al, 2010;Ternon et al, 2010). Such fast-sinking POC, negligible within the euphotic zone, is sufficient to explain deep-ocean POC fluxes (Honda and Watanabe, 2010;Riley et al, 2012); this emphasizes the importance of the mode by which carbon is transferred downward when considering carbon flux parameterization.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…The slope of the particle-size spectrum is highly variable (Guidi et al, 2009). Measurements have shown that the majority of the flux is composed of slow (< 10 m day −1 ) and fast (> 350 m day −1 ) sinking particles (Riley et al, 2012;Alonso-Gonzalez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%